A STUDY ON CLINICAL PATTERN OF DERMATOSES IN PAEDIATRIC AGE GROUP IN A TERTIARY CARE HOSPITAL IN ASSAM - Divya J N, Bhaskar Gupta, Johnson Cyriac , Joydeep Roy, Arup Paul, Shromona Kar, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Paediatric dermatoses are a distinct group of disorders,comprising skin problems encountered during both childhood and adolescence. Skin diseases are a major health problem in the paediatric age group and areassociated with significant morbidity and mortality.